Increased Expression of HCN Channels in the Ventricular Myocardium Contributes to Enhanced Arrhythmicity in Mouse Failing Hearts. Issue 3 (24th May 2013) - Kuwabara, Yoshihiro; Kuwahara, Koichiro; Takano, Makoto; Kinoshita, Hideyuki; Arai, Yuji; Yasuno, Shinji; Nakagawa, Yasuaki; Igata, Sachiyo; Usami, Satoru; Minami, Takeya; Yamada, Yuko; Nakao, Kazuhiro; et al.
Abstract : Background: The efficacy of pharmacological interventions to prevent sudden arrhythmic death in patients with chronic heart failure remains limited. Evidence now suggests increased ventricular expression of hyperpolarization‐activated cation (HCN) channels in hypertrophied and failing hearts contributes to their arrythmicity. Still, the role of induced HCN channel expression in the enhanced arrhythmicity associated with heart failure and the capacity of HCN channel blockade to prevent lethal arrhythmias remains undetermined. Methods and Results: We examined the effects of ivabradine, a specific HCN channel blocker, on survival and arrhythmicity in transgenic mice (dnNRSF‐Tg) expressing a cardiac‐specific dominant‐negative form of neuron‐restrictive silencer factor, a useful mouse model of dilated cardiomyopathy leading to sudden death. Ivabradine (7 mg/kg per day orally) significantly reduced ventricular tachyarrhythmias and improved survival among dnNRSF‐Tg mice while having no significant effect on heart rate or cardiac structure or function. Ivabradine most likely prevented the increase in automaticity otherwise seen in dnNRSF‐Tg ventricular myocytes. Moreover, cardiac‐specific overexpression of HCN2 in mice (HCN2‐Tg) made hearts highly susceptible to arrhythmias induced by chronic β‐adrenergic stimulation. Indeed, ventricular myocytes isolated from HCN2‐Tg mice were highly susceptible to β‐adrenergic stimulation‐induced abnormal automaticity, which was inhibited by ivabradine. Conclusions: HCN channel blockade by ivabradine reduces lethal arrhythmias associated with dilated cardiomyopathy in mice. Conversely, cardiac‐specific overexpression of HCN2 channels increases arrhythmogenicity of β‐adrenergic stimulation. Our findings demonstrate the contribution of HCN channels to the increased arrhythmicity seen in failing hearts and suggest HCN channel blockade is a potentially useful approach to preventing sudden death in patients with heart failure.